2019
DOI: 10.3748/wjg.v25.i24.2977
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for hepatocellular carcinoma: Current and future

Abstract: Hepatocellular carcinoma (HCC) arises on the background of chronic liver disease. Despite the development of effective anti-viral therapeutics HCC is continuing to rise, in part driven by the epidemic of non-alcoholic fatty liver disease. Many patients present with advanced disease out with the criteria for transplant, resection or even locoregional therapy. Currently available therapeutics for HCC are effective in a small minority of individuals. However, there has been a major global interest in immunotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 101 publications
0
153
0
2
Order By: Relevance
“…Most studies on ex vivo DC vaccines employ a similar procedure: first, mononuclear cells are isolated from peripheral blood and transferred into cell culture. Then, DCs are stimulated with activating cytokines such as granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-4 and TNF-α and the exposure to a specific antigen is induced, usually by incubation with either tumor lysates or TAAs, but methods of cell fusion or tumor-associated RNA or DNA transfection have also been described [ 129 , 145 ]. Subsequently, the activated DCs are transferred to the patient where the injection of mature, antigen-loaded DCs results in the induction of both CD8+ cytotoxic T cells and CD4+ Th cells, particularly IFN-γ-producing Th1 cells [ 129 , 146 ].…”
Section: Immunological Therapeutic Approachesmentioning
confidence: 99%
“…Most studies on ex vivo DC vaccines employ a similar procedure: first, mononuclear cells are isolated from peripheral blood and transferred into cell culture. Then, DCs are stimulated with activating cytokines such as granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-4 and TNF-α and the exposure to a specific antigen is induced, usually by incubation with either tumor lysates or TAAs, but methods of cell fusion or tumor-associated RNA or DNA transfection have also been described [ 129 , 145 ]. Subsequently, the activated DCs are transferred to the patient where the injection of mature, antigen-loaded DCs results in the induction of both CD8+ cytotoxic T cells and CD4+ Th cells, particularly IFN-γ-producing Th1 cells [ 129 , 146 ].…”
Section: Immunological Therapeutic Approachesmentioning
confidence: 99%
“…ICI therapy was recently approved as second-line therapy for HCC (Table 1) (7,9). Other promising immunotherapies are in development and are aimed at boosting existing or de novo immune responses, including vaccines and oncolytic viruses, and combination ICI therapy (167). Anticipation awaits the results of NCT03298451, a phase 3 clinical trial assessing anti-PD-L1 and anti-CTLA-4 combination therapy vs. monotherapy as better first-line options than sorafenib [HIMALAYA trial, (NCT03298451)].…”
Section: Liver Cancermentioning
confidence: 99%
“…Immune checkpoint proteins including the programmed cell death protein 1 (PD-1/PDCD1), programmed death-ligand-1 (PD-L1/CD274), and cytotoxic T-lymphocyte associated antigen 4 (CTLA-4) are established prognostic markers for LC patients (Cariani and Missale, 2019;El Dika et al, 2019;Johnston and Khakoo, 2019). Recent studies showed that tumor mutation burden (TMB) is also significantly associated with the susceptibility to anti-tumor immunotherapy, and a higher TMB indicates better prognosis in many cancer types (Peng et al, 2019;Wang and Li, 2019).…”
Section: The M6a-related Nomogram Has High Predictive Powermentioning
confidence: 99%